2021
DOI: 10.1155/2021/5573237
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial and Antioxidant Roles of Buckwheat Honey (BH) in Liquid Preservation of Boar Semen

Abstract: In the present study, we hypothesized that buckwheat honey (BH) should be regarded as a potential alternative to antibacterial and antioxidant agent in liquid storage of boar semen. To this end, boar semen was firstly studied for in vitro dose tolerability to BH by measuring sperm progressive motility. The optimum progressive motility of boar spermatozoa was observed in extender with 0.5% and 0.6% BH addition. Afterward, sperm quality parameters, bacterial profile and composition, total antioxidant (T-AOC), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A recent study determined that adding 0.5 and 0.6% buckwheat honey significantly improved sperm motility, acrosome integrity, plasma membrane integrity, inhibition of opportunistic bacterial growth, and altered microbial composition at the storage end. In addition, the levels of total antioxidant capacity, catalase, and superoxide dismutase enzymes are higher with buckwheat honey [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study determined that adding 0.5 and 0.6% buckwheat honey significantly improved sperm motility, acrosome integrity, plasma membrane integrity, inhibition of opportunistic bacterial growth, and altered microbial composition at the storage end. In addition, the levels of total antioxidant capacity, catalase, and superoxide dismutase enzymes are higher with buckwheat honey [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is mostly a mixture of sugars and water, containing a rich blend of proteins and secondary metabolites [13], and is renowned for its antibacterial properties [14,15]. It has been previously used as a semen extender additive in rams [16,17], humans [18], stallions [19], bulls [20,21], and boars [22] but still untested in rabbits. Another candidate tested was a combination of β-carotene and α-tocopherol.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the detrimental effects of OS on semen storage, various antioxidants were added into the semen extender, and their protective effect on sperm quality was observed [ 11 , 33 , 34 ]. Furthermore, our previous investigation demonstrated that antioxidants in seminal plasma are directly involved in cryotolerance of boar spermatozoa by playing against OS induced by the freezing and thawing process [ 4 ].…”
Section: Discussionmentioning
confidence: 99%